2018
DOI: 10.1016/s1470-2045(18)30099-8
|View full text |Cite
|
Sign up to set email alerts
|

Medication overuse in oncology: current trends and future implications for patients and society

Abstract: Summary: The high cost of cancer care worldwide is largely attributable to rising drugs prices. Despite their high costs and potential toxicities, anticancer treatments may be subject to overuse, defined as the provision of medical services that are more likely to harm than to benefit a patient. We found 30 studies documenting medication overuse in cancer, which included 16 examples of supportive medication overuse and 17 examples of anti-neoplastic medication overuse in oncology. Evaluated drugs were limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 92 publications
0
25
0
2
Order By: Relevance
“…The discussion about changing the focus of treatment to providing symptomatic and supportive care is complex. Little literature addresses the magnitude of financial, psychological, or physical harms of medication overuse in cancer, even when it could be substantial [ 45 ]. Smith and Hillner have proposed for patients with advanced cancer, changes in medical oncologists’ behavior, and changes in their attitudes and practices that will bend the cancer-cost curve [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The discussion about changing the focus of treatment to providing symptomatic and supportive care is complex. Little literature addresses the magnitude of financial, psychological, or physical harms of medication overuse in cancer, even when it could be substantial [ 45 ]. Smith and Hillner have proposed for patients with advanced cancer, changes in medical oncologists’ behavior, and changes in their attitudes and practices that will bend the cancer-cost curve [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is surprising given how many services have been identi ed as low-value in cancer care. The lack of de-implementation interventions to reduce low-value care may explain why low-value cancer care persists, despite signi cant forces over the past decade to reduce low-value care [13,14]. While educational campaigns and medical guidelines have shown some potential in raising awareness regarding low-value services in cancer care [26], recent studies demonstrate that, in many areas, those recommendations had a limited effect on reducing low-value care [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Medical societies have developed several guidelines and recommendations pertaining to low-value tests, treatments, and follow-up processes across the cancer care continuum [10][11][12]. However, recent reviews found that a considerable proportion of services that cancer patients receive could still be classi ed as low-value [13,14]. For example, both the American Society for Clinical Oncology and Choosing Wisely Canada [15,16] recommend not to use imaging in early-stage breast cancer; despite these recommendations, about one-third of early-stage breast cancer patients underwent at least one advanced imaging exam (e.g., bone scan, positron-emission tomography) for staging [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the definition of the diagnostic and therapeutic strategy for melanoma patients involves choosing between multiple alternative courses of action that impact cost structure and performance for patient survival. On the other hand, for most healthcare systems, the unaffordability of new technologies is a widespread phenomenon [ 3 ], and a large percentage of patients have restricted access to the necessary healthcare resources [ 4 , 5 ]. In particular, Brazil has a population of over 200 million, and almost 76% of the population have to rely exclusively on public healthcare, which is very limited regarding access to health innovations and medical aid [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%